(untitled) (Journal of the College of Basic Education, 2024)
Pseudomonas aeruginosa is considered as the most common gram-negative bacteria that infect hospitalized patients. One hundred sixty six specimens of wound discharge were collected during the period from October to December 2022. Thirty isolates of Pseudomonas aeruginosa have been identified via the cultural, morphological, and biochemical tests. Vitek-2 compact system used to determine the most accurate identification for Pseudomonas aeruginosa, and thirty isolates of Pseudomonas aeruginosa were recognized. In the present study, Pseudomonas aeruginosa was detected in 32.25% of the isolates. All isolates were subjected to antibiotic susceptibility tests to determine their susceptibility to 14 different antibiotics. The results showed total resistance to piperacillin (100%), high resistance rates to ceftazidime (96.7%), tobramycin (96.7%), gentamicin (80%), piperacillin-tazobactam (70%), aztreonam (66.7%), cefoperazone (66.7%), and amikacin (60%). Low resistance rates were found for imipenem (30%), meropenem (43.3%), and gatifloxacin (46.7%), but there was moderate resistance to ciprofloxacin (53.3%), cefotaxime (50%) and colistin (50%). The current investigation determined that among 30 isolates of Pseudomonas aeruginosa, six (20%) developed a weak biofilm, nine (30%) formed a moderate biofilm, and fifteen (50%) formed a strong biofilm. The findings of the present investigation revealed that the vast majority of the isolates with significant antibiotic-resistance can create biofilms.